2001
DOI: 10.1038/sj.ijir.3900773
|View full text |Cite
|
Sign up to set email alerts
|

Decreased penile erection in DOCA-salt and stroke prone-spontaneously hypertensive rats

Abstract: Numerous etiological studies have established a positive clinical association between hypertension and erectile dysfunction. However, to date, the mechanism underlying this dysfunction remains to be established. In this study, we demonstrate the presence of erectile dysfunction in two rat models of hypertension, and hypothesize that increased vasoconstrictor signaling via Rhokinase contributes to the decreased erectile response. We found deoxycorticosterone-salt and stroke prone-spontaneously hypertensive rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 31 publications
5
55
0
Order By: Relevance
“…Additionally, recent data from DOCA-salt and stroke-prone-spontaneously hypertensive rats have demonstrated a decreased erectile response associated with hypertension. 12 In the last few years, therapeutic intervention against the renin-angiotensin-aldosterone system (RAAS), by both angiotensin I converting enzyme (ACE) inhibitors and more recently through angiotensin II type 1 (AT1) receptor antagonist, has been increasing in acceptance as a useful antihypertensive therapy worldwide. Candesartan cilexetil, a potent, highly selective AT1 receptor antagonist with insurmountable binding properties and slow off-rate from the receptor, has demonstrated to be effective and well tolerated when used in moderate or severe hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent data from DOCA-salt and stroke-prone-spontaneously hypertensive rats have demonstrated a decreased erectile response associated with hypertension. 12 In the last few years, therapeutic intervention against the renin-angiotensin-aldosterone system (RAAS), by both angiotensin I converting enzyme (ACE) inhibitors and more recently through angiotensin II type 1 (AT1) receptor antagonist, has been increasing in acceptance as a useful antihypertensive therapy worldwide. Candesartan cilexetil, a potent, highly selective AT1 receptor antagonist with insurmountable binding properties and slow off-rate from the receptor, has demonstrated to be effective and well tolerated when used in moderate or severe hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…The pathological changes resulting from altered vascular function include injury to the brain, kidney and heart (55). Several studies have established a clinical correlation between incidence of hypertension and ED (58). According to Buccchardt et al, 30% of hypertensive patients have ED and the severity of this sexual disorder is directly proportional to the severity of hypertension.…”
Section: Hypertension and Edmentioning
confidence: 99%
“…We have previously reported that this same compound lowers blood pressure when high doses are given by intracavernous injection to normal, intact rats 10 or to severely hypertensive rats. 21 Other investigators have reported that oral administration of Y-27632 lowers blood pressure in hypertensive rats but not in normotensive animals. 14 The present study utilizes the castrated rat with 1000 mg Y-27632 applied to the glans penis and surrounding skin.…”
Section: Rho-kinase Inhibitor In Penile Erectionmentioning
confidence: 99%